A Review on Sustainable Construction Regulations in Asian Countries: Savvy Insights for Indonesia - Maria Agnes; Raldi Hendro Koestoer (School of Postgraduate Studies, Diponegoro Univer, 2021)
Infrastructure projects, more specifically the construction, operation and deconstruction phase, are claimed to have the potential to cause profound impacts on the environment. The construction industry worldwide attains to generate the consumption for 40% of total energy production and 16% of the entire sum of water volume available, as well as the production for 25% of greenhouse gas emissions and 30-40% of all solid wastes. This circumstance has led to the rising of global awareness with regards to the importance of sustainability concept implementation in the construction industry which subsequently resulted in the formulation of corresponding laws and regulations in recent years. Indonesia is no exception. Decree of the Minister of Public Works and Public Housing of the Republic of Indonesia No: 05/PRT/M/2015 concerning General Guidelines for the Implementation of Sustainable Construction in Infrastructure Projects Execution has been enacted to provide a direction for sustainable construction implementation that creates sustainable infrastructure, which will eventually contribute to a sustainable development. Based upon the decree, this study conducts a literature review on the implementation process of laws and regulations related to sustainable construction in Asian countries. The review contains exploratory case studies and comparative analysis on general overview of the regulations format and the challenges encountered, as well as strategies taken, during the implementation process. This paper provides a useful reference for policy makers in Indonesia, while simultaneously benefits the construction industry practitioners and other related stakeholders. ABSTRAKPenyelenggaraan infrastruktur, khususnya pada tahapan pelaksanaan konstruksi, pemanfaatan dan pembongkaran, memberikan dampak negatif yang cukup signifikan terhadap lingkungan. Sektor industri konstruksi tercatat berkontribusi atas penggunaan 40% total produksi energi di dunia, 16% total jumlah konsumsi air, 25% emisi gas Rumah Kaca (GRK), serta 30–40% dari volume limbah padat dunia. Kondisi ini telah disadari oleh negara-negara di dunia, termasuk Indonesia, sehingga ditindaklanjuti dengan diterbitkannya regulasi-regulasi sehubungan dengan konstruksi berkelanjutan. Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat Republik Indonesia (Permen PUPR) Nomor: 05/PRT/M/2015 tentang Pedoman Umum Implementasi Konstruksi Berkelanjutan Pada Penyelenggaraan Infrastruktur Bidang Pekerjaan Umum dan Permukiman telah diterbitkan untuk dapat dijadikan acuan bagi para penyelenggara infrastruktur dalam mengimplementasikan pendekatan konstruksi berkelanjutan di Indonesia. Mengacu kepada Permen tersebut, penelitian ini melakukan studi komparasi berdasarkan kajian literatur terhadap proses implementasi regulasi konstruksi berkelanjutan di beberapa negara Asia lainnya dengan tujuan tidak hanya untuk mengetahui format regulasinya namun juga tantangan-tantangan yang dihadapi dan strategi-strategi yang diambil dalam proses implementasinya. Hasil dari penelitian ini diharapkan dapat digunakan sebagai bahan pertimbangan penentuan kebijakan lanjutan sehubungan penyelenggaraan infrastruktur berkelanjutan di Indonesia.